Current perspectives: the impact of cyberbullying on adolescent health - Nixon CL (Dove Medical Press, 2014)
Charisse L Nixon Pennsylvania State University, the Behrend College, Erie, PA, USA Abstract: Cyberbullying has become an international public health concern among adolescents, and as such, it deserves further study. This paper reviews the current literature related to the effects of cyberbullying on adolescent health across multiple studies worldwide and provides directions for future research. A review of the evidence suggests that cyberbullying poses a threat to adolescents' health and well-being. A plethora of correlational studies have demonstrated a cogent relationship between adolescents' involvement in cyberbullying and negative health indices. Adolescents who are targeted via cyberbullying report increased depressive affect, anxiety, loneliness, suicidal behavior, and somatic symptoms. Perpetrators of cyberbullying are more likely to report increased substance use, aggression, and delinquent behaviors. Mediating/moderating processes have been found to influence the relationship between cyberbullying and adolescent health. More longitudinal work is needed to increase our understanding of the effects of cyberbullying on adolescent health over time. Prevention and intervention efforts related to reducing cyberbullying and its associated harms are discussed. Keywords: cyberbullying, adolescent health, prevention, intervention